(untitled) (Research, Society and Development, 2022)
Report of a gastronomic experience carried out with a Group of Women from the Community of São Pedro Frio, rural area of the municipality of Colatina, state of Espírito Santo, Brazil, during the Meeting “Sabor e Prosa”. This meeting descended from a project that aimed to study the ecotourism potential of São Pedro Frio through the method of building socio-environmental cartographies, as a proposal for participatory research. Food plays a fundamental role in human life and the incentive to offer healthy food has expanded among different sectors. Currently, gastronomy has taken on other proportions, including recreational, artistic and health. The experience was carried out in two stages, face-to-face and through telephone contacts. The trial was planned with a view to the use of natural resources linked to the concepts of sustainability and healthy eating. Integration was observed between the group and discussions on the use of ingredients such as unconventional food plant species. The menu presented, namely: tapioca canapé with mango jelly, ora-pro-nóbis leaf and jambo flower, prose fish (breaded tilapia fillet and rested in green filling), rice with basil and cashew nuts, red wine and natural grape juice. Gastronomic practices in rural communities that stimulate the gastronomic potential can serve as an instrument for the strengthening of a sustainable and healthy tourist gastronomy.